Social Dynamics in Swiss Society : Empirical Studies Based on the Swiss Household Panel - Tillmann, Robin; Voorpostel, Marieke; Farago, Peter; Tillmann, Robin; Voorpostel, Marieke; Farago, Peter (Cham Springer Nature, 2018)
Using longitudinal data from the Swiss Household Panel to zoom in on continuity and change in the life course, this open access book describes how the lives of the Swiss population have changed in terms of health, family circumstances, work, political participation, and migration over the last sixteen years. What are the different trajectories in terms of mobility, health, wealth, and family constellations? What are the drivers behind all these changes over time and in the life course? And what are the implications for inequality in society and for social policy? The Swiss Household Panel is a unique ongoing longitudinal survey that has followed a large sample of Swiss households since 1999. The data provide the rare opportunity to go beyond a snapshot of contemporary Swiss society and give insight into the processes in people$1 (Bs lives and in society that lie behind recent developments. ; This open access book provides an unique insight into the processes in people's lives and society Based on unique longitudinal data spanning 16 years (1999-2014) Contains several cross-national comparisons.s
English
Keywords: Social issues & processes; Sociology; Central government policies; Social sciences; Quality of life; Sociology; Social policy